2019
DOI: 10.3390/su11010265
|View full text |Cite
|
Sign up to set email alerts
|

Ecolabelling in the Romanian Seaside Hotel Industry—Marketing Considerations, Financial Constraints, Perspectives

Abstract: The tendency to implement diverse environmental tools and promote the adoption of environmentally friendly practices in tourism activities is relatively new. One such tool is the EU Ecolabel used in the hotel industry as a voluntary European initiative meant to attest to the responsible attitude towards the environment. Since holding the ecolabel by the Romanian accommodation units is rather an exception, our aim was to investigate the views of industry managers on environmental issues, focusing on the EU Ecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…Green certificates have a positive influence on a hotel's tendency to implement IoT technology, especially to satisfy B2B customers' positive attitudes towards green initiatives and specific energy saving initiatives. This driver is in line with several of the findings by [14,19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Green certificates have a positive influence on a hotel's tendency to implement IoT technology, especially to satisfy B2B customers' positive attitudes towards green initiatives and specific energy saving initiatives. This driver is in line with several of the findings by [14,19].…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has indicated that not only sustainable practices, but also environmental green certificates are components which can develop the green image of a hotel and ultimately represent a competitive advantage for the hotel. Green certificates (e.g., the EU Ecolabel) may improve the hotel's relationships with its close stakeholders, like customers and suppliers [18], but also result in an improved corporate image and reputation among the general public [5,19]. It is also important to integrate internal stakeholders, the managers and employees, in the educational efforts to increase sustainability awareness and specific knowledge, including specific training programs about environmental protection [5,20].…”
Section: Sustainability and Hotelsmentioning
confidence: 99%
“…Barbulescu et al [33] showed that hotel managers in Romania implemented environmental management applications to save power and water and to minimize waste. The hotel managers who participated in their study stated that environmental management applications provided competitive advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the impact of eco-labelling have focused on several directions: the advantages of eco-labelling for tourism companies, the tourism industry, and tourists, the difficulties that companies face when trying to obtain such a certification, and the impact of holding an eco-label on consumers' decisions. There are also less investigated aspects, such as those regarding the real advantages that an ecolabel brings to tourism businesses, although the theoretical advantages are listed in several works [33]. The second aim of this paper, in this context, was to reveal the impact of eco-labelling activities on accommodation establishments.…”
Section: Introductionmentioning
confidence: 99%
“…With several exceptions (Italy with 159 Ecolabelled hotels, France 92, Spain 59, Austria 36 and Switzerland 10), most European countries have only several hotels with this label (European Commission, 2017a). Bărbulescu, Moraru and Duhnea (2019) underscore that "even if managers are aware that EU Ecolabel represents a comparative advantage", the additional costs, difficulty to meet the criteria and also its voluntary character represent real barriers, preventing the widespread presence of such EU Ecolabelled hotels in Romania.…”
Section: Intercontinental/ Responsible Business Report 2018 Sustainabmentioning
confidence: 99%